2010
DOI: 10.1177/0022034510377336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Respiration on Soft Palate Movement in Feeding

Abstract: Cyclic soft palate elevation is temporally associated with masticatory jaw movement. However, the soft palate is normally lowered during nasal breathing to maintain retropalatal airway patency. We tested the hypothesis that the frequency and amplitude of soft palate elevation associated with mastication would be reduced during inspiration. Movements of radiopaque soft palate markers were recorded by videofluorography while 11 healthy volunteers ate solid foods. Breathing was monitored with plethysmography. Mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…This soft palate elevation can also oppose respiration by narrowing the pharyngeal airway. Our previous study showed that this masticatory soft palate elevation is diminished during inspiration [21], probably due to its role in maintaining the retro-palatal airway during inspiration. These findings suggest that the control of breathing has a significant interaction with control of tongue and soft palate motion during mastication and stage II transport, as it does in swallowing.…”
Section: Discussionmentioning
confidence: 91%
“…This soft palate elevation can also oppose respiration by narrowing the pharyngeal airway. Our previous study showed that this masticatory soft palate elevation is diminished during inspiration [21], probably due to its role in maintaining the retro-palatal airway during inspiration. These findings suggest that the control of breathing has a significant interaction with control of tongue and soft palate motion during mastication and stage II transport, as it does in swallowing.…”
Section: Discussionmentioning
confidence: 91%
“…To assess swallowing, studies variously use videofluoroscopy exams (5)(6)(7)11,14,18,19) , digital acoustic analysis of swallowing sounds (9,21) and surface electromyography (11) . The use of control groups and participants' ages also varied among the reviewed studies.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that aspiration is not a normal finding in VF exams of healthy subjects. A third experimental study (7) examined the effect of the respiratory phase on the soft palate movement during feeding. With the assumption that the elevation of the soft palate that is associated with mastication would be reduced during inspiration, the authors described how the respiratory phase is integrated with soft palate movement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, kinematic measures are simplified by attaching small radiopaque markers on the mucosal surface. This technique enables to trace the movements of the tongue or soft palate [5, 1113]. In our previous studies, small lead discs (5-mm diameter) were used as the radiopaque markers, and were attached to the tooth surface with dental cement, and to the tongue surface with medical adhesive [14] (Fig.…”
Section: Vfs Equipment Settings and Techniquesmentioning
confidence: 99%
“…The main feature of videofluoroscopic analysis is to assess the kinesiology of food bolus and oropharyngeal structures using temporal and spatial measurements. Moreover, synchronizing VFS with the other physiological assessments such as electromyography [3], manometry [4], respiratory measurements[5, 6](airflow or plethysmography), enables analysis of the integrated physiology of eating, drinking, swallowing, and breathing.…”
Section: Introductionmentioning
confidence: 99%